METHODOLOGICAL ASPECTS OF ECOLOGICAL RATING FOR CHANGES OF GROUND WATER LEVELS - KOSHLIAKOV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The conceptual bases of methodology of research and forecasting of changes of levels of ground waters for a rating of ecological safety of separate ground water systems are stated in view of risk.